2008
DOI: 10.1002/elps.200800015
|View full text |Cite
|
Sign up to set email alerts
|

Difference gel electrophoresis analysis of Ras‐transformed fibroblast cell‐derived exosomes

Abstract: Exosomes are membrane vesicles of endocytic origin released by many cell types. The molecular composition of exosomes reflects the specialised functions of their original cells. For example, these vesicles can mediate communication through their ability to bind to target cells, facilitating processes such as vascular homeostasis and antigen presentation. Although the proteomes of exosomes from several cell types are known, exploration of exosomes from additional cell types may improve our understanding of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 45 publications
5
42
1
Order By: Relevance
“…HRAS and NRAS have been found in exosomes purified from transformed cells (41,42) and urine (43). HRAS, NRAS, and KRAS were previously detected in exosomes via LC-MS/ MS; however, that study did not describe the peptides identified, and further validation was not provided (44).…”
Section: Discussionmentioning
confidence: 95%
“…HRAS and NRAS have been found in exosomes purified from transformed cells (41,42) and urine (43). HRAS, NRAS, and KRAS were previously detected in exosomes via LC-MS/ MS; however, that study did not describe the peptides identified, and further validation was not provided (44).…”
Section: Discussionmentioning
confidence: 95%
“…Over the past decade, our laboratory has accumulated exhaustive proteomic profiling data sets for highly purified EV subtypes (exosomes and sMVs) from the human colon cancer cell lines LIM1863 (35, 37, 66), HCT116, SW1222, LIM1215 (102), SW480, SW620 (74), human NIH3T3 fibroblast, and Rastransformed NIH3T3 fibroblast cells (103), and the Madin-Darby canine kidney (MDCK) cell line and an MDCK cell line transformed with oncogenic H-Ras (21D1 cells) (4). These extensive proteomic data sets (RAW files) are publically accessible through PeptideAtlas (104).…”
Section: Isolation Of Evs From Body Fluidsmentioning
confidence: 99%
“…(B) Dying or apoptotic cells release shedding microvesicles in the early stages of apoptosis and larger apoptotic bodies at later times that contain nuclear and cytoplasmic remnants of the degrading cell. stress (93), stimulation with cytokines (139), exposure to ATP (17), cell death (61), hypoxia (119), transformation (45), expression of oncogenes (6,27,78), and viral infection (11,88,102,140,162). Thus, in addition to the two defined MVB populations, one destined for a lysosomal degradation and the other for exosomal secretion, it is likely that additional MVB populations produce exosomes with distinct compositions.…”
Section: Fig 1 Microvesicle Biogenesis Pathways (A)mentioning
confidence: 99%